Mapuche and the Struggle for Autonomy in Chile, 1990-2005 [Los Mapuche y Las Lucha por la Autonomia en Chile, 1990-2005] - Canales-Tapia, P (Universidade Estadual de Ponta Grossa, Editora, 2016)
This work focuses in history and discourse of the Mapuche movement in Chile over the last two decades. In this sense, this proposal has as theoretical framework the debate on colonialism and decolonization processes in Latin America; and methodological terms, this research draws its analysis from the historical method and source criticism.